Complete mitochondrial genome of Black Drongo Dicrurus macrocercus (Passeriformes: Dicruridae) and phylogenetic analyses. Issue 8 (3rd August 2021) - Zhang, Haibo; Gou, Xue; Li, Shize; Wang, Cheng; Peng, Caichun; Hu, Canshi; Zhang, Mingming; Yu, Lifei; Su, Haijun
Abstract: The Black Drongo Dicrurus macrocercus is a bird belonging to the group Passeriformes, distributed almost all over the country in China. The conservation status of this species is Least Concern (LC) in IUCN. In this study, the complete mitogenome of D. macrocercus was determined. The mitochondrial DNA is packaged in a compact 17, 056 based pair (bp) circular molecule with A + T content of 57.04%. It contains 37 typical mitochondrial genes, including 13 protein-coding genes, 2 rRNAs and 22 tRNAs, and 1 non-coding regions. We reconstructed a phylogenetic tree based on mitogenome sequences of 15 Dicruridae species and one outgroup. In trees, D. macrocercus was clustered as an independent clade with high support value (100). The new mitogenome data would provide useful information for application in conservation genetics and further clarify the phylogenetic evolution of this species.